Didactic Games for Teaching Information Theory - Forišek, Michal; Steinová, Monika (Teaching Fundamental Concepts of Informatics, 2010)
We developed a set of didactic games and activities that can be used to illustrate and teach various concepts from Information Theory. For each of the games and activities we list the topics it covers, give its rules and related information, describe our practical experiences and give an overview of its scientific background. We also discuss the proper ways to integrate these games into the knowledge acquisition process.